Returns to basic skills in Central and Eastern Europe: A semi-parametric approach - Kevin Denny; Orla Doyle (University College Dublin, Department of Economics, 2005)
This paper uses semi-parametric econometric techniques to investigate the relationship between basic skills and earning in three post-communist countries: the Czech Republic, Hungary and Slovenia using the IALS dataset. While the large increases in the returns to education in the new market economies has been well documented in the literature, no study to date has examined the impact of basic skills and schooling on income. Estimating a Mincer human capital model we find that including a measure of basic skills reduces the returns to education. In addition, using a partial linear model in which log earnings is linear in schooling, but is an arbitrary function of basic skills, we find that this relationship is not well described by the common assumption of linearity at the tails of the distribution.
hdl:10197/97
Keywords: J31; 330; Earnings; Education; Basic skills; Transition